2007
DOI: 10.5194/acp-7-5081-2007
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of immersion mode ice nucleation on surrogates of mineral dust

Abstract: Abstract.A differential scanning calorimeter (DSC) was used to explore heterogeneous ice nucleation of emulsified aqueous suspensions of two Arizona test dust (ATD) samples with particle diameters of nominally 0-3 and 0-7 µm, respectively. Aqueous suspensions with ATD concentrations of 0.01-20 wt% have been investigated. The DSC thermograms exhibit a homogeneous and a heterogeneous freezing peak whose intensity ratios vary with the ATD concentration in the aqueous suspensions. Homogeneous freezing temperatures… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
402
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 289 publications
(428 citation statements)
references
References 41 publications
25
402
0
1
Order By: Relevance
“…In investigations with continuous-flow diffusion chambers (Welti et al, 2012;Lüönd et al, 2010), many particles are investigated individually and a less steep temperature dependence of heterogeneous nucleation rates compared with the homogeneous case is observed. However, there is strong evidence that the surfaces of most ice-nucleating particles are not uniform with respect to their ability to nucleate ice (e.g., Marcolli et al, 2007;Vali, 2014). Refreeze experiments show that variations of the freezing temperatures between runs are much smaller than the range covered by freezing experiments with many droplets, in accordance with the assumption that specific sites are responsible for freezing (Vali, 2008(Vali, , 2014Peckhaus et al, 2016).…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…In investigations with continuous-flow diffusion chambers (Welti et al, 2012;Lüönd et al, 2010), many particles are investigated individually and a less steep temperature dependence of heterogeneous nucleation rates compared with the homogeneous case is observed. However, there is strong evidence that the surfaces of most ice-nucleating particles are not uniform with respect to their ability to nucleate ice (e.g., Marcolli et al, 2007;Vali, 2014). Refreeze experiments show that variations of the freezing temperatures between runs are much smaller than the range covered by freezing experiments with many droplets, in accordance with the assumption that specific sites are responsible for freezing (Vali, 2008(Vali, , 2014Peckhaus et al, 2016).…”
Section: Introductionmentioning
confidence: 90%
“…1 typical thermograms of emulsion measurements with Hoggar Mountain dust (panel a), ATD (panel b), and birch pollen washing water (panel c) are shown. For ATD, Marcolli et al (2007) showed that the observed range of heterogeneous freezing temperatures cannot be described by assuming the same contact angle for all ATD particles. Rather, the ice-nucleating sites of ATD particles are required to be of different qualities.…”
Section: Emulsion Measurementsmentioning
confidence: 99%
“…When the ice particles are evaporated, we delete this ice size class and the number density is put back into the original liquid size class from which the ice particles nucleated. Besides homogeneous nucleation the model also calculates heterogeneous ice nucleation on ice nuclei, assumed to be mineral dust particles in the immersion mode, similar to the approach by Engel et al (2013) using the active-site-based heterogeneous nucleation parameterization of Marcolli et al (2007). Sedimentation of the ice crystals within the column is taken into account by means of a size-dependent terminal velocity, moving a fraction of them into boxes at lower levels (in vertically stacked Eulerian bins of 100 m depth).…”
Section: Ice Microphysics Schemementioning
confidence: 99%
“…ZOMM has been used previously for heterogeneous ice nucleation in the immersion mode (see Engel et al (2013)) and we closely follow their treatment. For technical details, see Appendix C. We follow Marcolli et al (2007) and describe the nucleation process using active site theory. The mean area of an active site is assumed to be A as = 10 nm 2 .…”
Section: Heterogeneous Nucleation Of Icementioning
confidence: 99%
See 1 more Smart Citation